In the choice between health and money, health comes first: an analysis of happiness among rural Chilean elderly - German Lobos; Maria del Carmen Lapo; Berta Schnettler (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2016)
Abstract: We studied the relationship between happiness and individual socio-demographic context and health and dietary variables by interviewing 389 elderly individuals (age 60-90 years) living in rural areas in the Maule Region of Central Chile. The Lyubomirsky & Lepper (1999) subjective happiness scale was used. Ordinal logistic regression models were estimated. The discrete dependent variable was level of happiness. The following variables were significantly associated with happiness: (1) individual socio-demographic variables like age and satisfaction with the economic situation; (2) health variables like independence in activities of daily living, common activities, and self-rated health; and (3) dietary variables such as life satisfaction related to food and the frequency with which the elders shared dinner with others. The study results suggest more efficient efforts at healthy eating for the elderly in rural areas.